Pembimbingan Klien Balai Pemasyarakatan Klas I Medan melalui Konsep Rumah Singgah “Griya Abhipraya” - Joy Nicholas Matthew Sigalingging; Hairani Siregar (JOURNAL SAINS STUDENT RESEARCH, 2024)
This final project is the result of the author's work aimed at fulfilling the requirements for the Field Work Practice 2 course at Class I Medan Penitentiary. The author conducted observations and actively participated in the Griya Abhipraya program organized by Class 1 Medan Penitentiary. In its implementation, clients were given the freedom to choose between participating in the Griya Abhipraya activities or adhering to mandatory reporting activities while seeking their own sources of income. The author worked with a group of clients with diverse criminal cases, applying the stages of social group work from preparation (engagement, intake, and contract) to termination. The research method used was Focus Group Discussion (FGD). The final result of this project indicates that clients are confident in participating in the Griya Abhipraya program organized by Class 1 Medan Penitentiary as their shelter.